Peran Wajib Pajak Kendaraan Bermotor Atas Kebijakan Pemutihan Pajak dan Pajak Emisi Karbon di Kabupaten Karawang - Tania Meilani; Lilis Lasmini; Fista Apriani Sujaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tax whitening policies and motor vehicle carbon emission policies are one of the things that need to be considered, where the tax whitening policy must be seen as to the effectiveness of the policy and the carbon emission tax must be structured so that it can be accepted by the public. This research was conducted with the aim of knowing, analyzing and explaining the tax whitening policy and vehicle carbon emissions tax policy in Karawang Regency. This research uses a qualitative research approach with descriptive analysis methods. Research data was taken through field observations, interviews and literature studies. Based on the results and discussion, it was found that the effectiveness of the Vehicle Tax Reduction Program in Karawang, which is carried out regularly every year and socialization is carried out through various media, has succeeded in creating enthusiasm and community participation. This positive response can be seen from the increase in tax revenue and active taxpayer participation during the tax whitening period. If the vehicle carbon emissions tax policy is implemented in Karawang Regency, it has the potential to reduce pollution levels by 10%. However, taxpayers have had little response to this policy because it will increase the amount of responsibility for paying vehicle tax. The conclusion confirms that the tax whitening program is effective in achieving tax revenue objectives and stimulating community participation. The carbon emissions tax policy still needs to be thoroughly disseminated to the public so that the main objectives of the policy are conveyed well.